Pengaruh Keputusan Investasi, Kebijakan Dividen, dan Profitabilitas Terhadap Nilai Perusahaan - Tunisia Nur'aeti Erawan; Endang Taufiqurrahman (Peneliti.net, 2022)
This study aims to determine, analyz, and describe the effect of Investments Decisions, Dividend Policy, Profitability on Corporate Values to Properties And Real Estate Companies Listed On The Indonesia Stock Exchange For 2017-2021 Period. The method analysis used in this study is a verification descriptive analysis method and uses multiple linear regression analysis tools. The research population was 63 companies and 6 companies as sample with sampling technique is purposive sampling. Results of the study show that investment decisions not have significant impact on corporate value, dividend policy partially have significant impact on the corporate value, and profitability partially have significant impact on the corporate value. While results show that investment decisions, dividend policy, and profitability have significant impact on corporate value. Value of R2 is 0.766 which indicates that investment decisions, dividend policy, and profitability simultaneously affect the corporate value by 76,6% while the remaining 23,4% in influenced by variables outside the study.